Pengaruh Asymmetric Information Terhadap Efektifitas Mekanisme Pengurang Masalah Agensi - Zaenal Arifin (Sinergi: Kajian Bisnis dan Manajemen, 2007)
This research investigates the influence of asymmetric information to the effectiveness of agency problem-reduction mechanisms in Indonesian listing companies. Using samples of manufacturing companies in Jakarta Stock Exchange from 2001-2004, this research find out that asymmetric do have influence the effectiveness of dividend mechanism in reducing agency problem. The dividend mechanism effectives in reducing agency problem only if the level of asymmetric information is high. This research also find out that the debt mechanism and the independent board of direction mechanism do not effective in reducing agency problem whether the level of asymmetric information high or low. Keywords:    asymmetric information, agency problem, dividend, debt, and independent board of director